CONTINUING TEACHER EDUCATION AT UNIMONTES: CONTRIBUTION TO THE UNIVERSITY AND IMPLICATIONS FOR TEACHING HEALTH - Santos Moura, Dayse Magna; Vieira Moura, Alda Aparecida; Santos Moura, Eduardo Junio; Cardoso da Silva , Huagner (Revista Ciranda, 2022)
Theme of great discussions in the educational environment, the continuous training of teachers in service, has over the years caused great changes in the environment due to the requirements in the career of university professors. Human Sciences Center - CCH acquired in the years 2015 to 2020 and the implications of this training in the professional’s life regarding the health of the teacher. As specific objectives, we will investigate the situation in which the training of the professional took place regarding the structural issue at the time of the studies, reflect on the training policies for this professional and verify if the teacher acquired health/pathology problems during teacher training. . This research is justified by the need to expose to the student body and to the entire academic community, the importance of the struggle of professionals for continuing education at the Unimontes CCH. It is important to note that the CCH is the center that supports around 82% of the University’s courses. It should be noted that due to the problems caused by the Covid 19 pandemic period, the survey was adapted in the online format, due to the limitations of the moment. As a research technique, we used the questionnaire via google forms, which also due to the limitations of the period, was carried out only in the Pedagogy course, which has a large number of teachers in three departments, Internships and School Practices, Education and Method and Educational Techniques.